The true costs of food in Kenya and Vietnam: A conceptual framework - Benfica, Rui (International Food Policy Research Institute, 2024)
Sustainable food systems provide enough quality, healthy, and affordable food to all without imposing a burden on planetary and social boundaries. By this standard, it is quite clear that food systems in many countries are not sustainable as they generate substantial environmental, social, and health costs while failing to provide affordable food to all (FAO et al., 2020). This implies the need to have a good understanding of the extent to which those externalities are present in country specific food systems. The key challenge is that such externalities are not reflected in market prices (Baker et al., 2020), being therefore hidden factors to drivers of choices by market players, as the link between market activity and those social and environmental harms is not directly visible or reflected in the incentives that drive economic systems (UNFSS, 2021). Internalizing the externalities of the food systems will require the full estimation of costs, including the measurement of externalities through “True Cost Accounting” (TCA) approaches. This document provides the analytical framework for the application of approaches in a research study to measure the true costs of food in Kenya and Vietnam. It focuses on: o Key research questions, their relevance, and policy implications o How the TCA analytical framework fits in The Economics of Ecosystems and Biodiversity (TEEB) framework o Country selection and geographic focus – national, sub-national o Data requirements for estimating the true costs, including household surveys, workers’ surveys, externally compiled Global Impact Database (GID), and monetization factors. o A step-by-step process for estimating the true costs in the study area and country level GID analysis.